Without A Trace?: The Construction of the Traceless Outdoor Experience in the Online Communications of Leave No Trace Corporate Partners - Piepmeier, Aubree (2016)
This dissertation examines how the corporate partners of the Leave No Trace Center for Outdoor Ethics (LNTCOE) operating in the outdoors industry construct the experience of traceless outdoor recreation for their consumers. It draws on the theoretical frameworks of constitutive CSR communication to explore how communications construct complex versions of CSR reality. It uses textual analysis to identify how the online discourse of LNT partners perpetuate the seemingly radical claim of leaving no trace. The findings suggest that outdoor firms use a range of discursive strategies to construct this representation of reality, including the management of moral narratives, claims of exceptionalism, and manipulation of definitional boundaries.